Expression of p16INK4a Biomarker has a Diagnostic Value in Predicting the Progressivity of Precancerous Cervical Lesion - Indarti, Junita (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To evaluate clinical value of p16INK4a biomarker level, by doing p16INK4a immunocytochemistry staining, as a predictor of progressivity of precancerous cervical lesion. Method: Design of this research is case-control study which will be stratified. Research was conducted in Cytology Laboratorium, Gynecology Specialistic Division, Department of Obstetrics and Gynecology, Dr. Cipto Mangunkusumo Hospital from August 2007 to September 2008. Immunocytochemistry examination was conducted in Anatomic Pathology Department, Dr. Hasan Sadikin Hospital. We divided the sample into two categories; patients with and without cervical intraepithelial neoplasia (CIN). This research will evaluate HPV infection and p16INK4a biomarker by doing p16INK4a immunocytochemistry (ICC) staining. Results: We have done immunocytochemistry examination in 130 patients, 26 without CIN and 104 with CIN. Immunocytochemistry cut-off point level is 50, which means value < 50 means low (L) p16INK4a expression and in reverse, value â¥ 50 means high (H) p16INK4a expression. The bivariate analysis of our study were p16INK4a (H) expression has the risk of CIN 1 with OR 8.4, for CIN 2 with OR 13 and for CIN 3 with OR 21, greater than p16INK4a (L) with all p values are significant. ICC p16INK4a (H) expression, age, number of sexual partners, and education are contributory to the risk of progressivity in CIN. The multivariate analysis demonstrates, ICC expression of p16INK4a (H) has a risk (OR) of CIN 1 17.19 times greater than p16INK4a (L); p16INK4a (H) expressionâs OR for CIN 2 is 25.56; and for OR CIN 3 is 37.32. The expression of p16INK4a has a significant p value and high OR, thus ICC expression of p16INK4a is suggested to be included in the algorithm of precancerous cervical lesion guidelines and scoring of probability of CIN as an alternative to HPV DNA considering less cost of the test. In this research, we found a scoring model to determine probability of progressivity in precancerous cervical lesion. Conclusion: The expression of p16INK4a has a diagnostic value in predicting the progressivity of precancerous cervical lesion. [Indones J Obstet Gynecol 2010; 34-3: 125-30] Keywords: p16INK4a expression, immunocytochemistry, predictor of progressivity, precancerous cervical lesion